Who succeeds and who fails? Exploring the role of background variables in explaining the outcomes of L2 language tests. (April 2023) - Gujord, Ann-Kristin Helland
This study explores whether and to what extent the background information supplied by 10, 155 immigrants who took an official language test in Norwegian affected their chances of passing one, two, or all three parts of the test. The background information included in the analysis was prior education, region (location of their home country), language (first language [L1] background, knowledge of English), second language (hours of second language [L2] instruction, L2 use), L1 community (years of residence, contact with L1 speakers), age, and gender. An ordered logistic regression analysis revealed that eight of the hypothesised explanatory variables significantly impacted the dependent variable (test result). Several of the significant variables relate to pre-immigration conditions, such as educational opportunities earlier in life. The findings have implications for language testing and also, to some extent, for the understanding of variation in learning outcomes.